A Research Project with Important Practitioner-Oriented Findings. - Glass, Robert L. (Communications of the ACM, 2007)
The article discusses a computing research project. College seniors were presented with basic requirements for a network project management software program and asked to produce a design in accordance with the ISO/IEC 9126 international standard for software product development. Ideally computer programmers would be able to create the application based on the students' designs. This turned out not to be the case. Various problems, including ambiguous and overlapping definitions, indicate the 9126 standard doesn't yet accomplish its aim.